Screening and selection of technologically applicable microorganisms for recovery of rare earth elements from fluorescent powder. (September 2018) - Hopfe, Stefanie; Konsulke, Silke; Barthen, Robert; Lehmann, Falk; Kutschke, Sabine; Pollmann, Katrin
Graphical abstract: Highlights: Leaching of hardly soluble REE-waste with microorganisms is possible. Highest leaching results with K. xylinus, L. casei and Y. lipolytica (up to 12.6%). Microbial produced organic acids contribute to leaching process. Direct leaching is more efficient than leaching with spent supernatant. Mainly red dye yttrium europium oxide is leached. Abstract: Rare Earth Elements (REE) are essential elements in many new technology products. Up to now, recycling is poorly established and no environmentally friendly strategies are applied. Modern biotechnologies like bioleaching can contribute to overcome the current limitations. In this study, we investigated bioleaching approaches exemplary for fluorescent phosphor (FP), which is accumulated during the recycling of fluorescent tubes and energy saving bulbs. A broad spectrum of different microorganisms were tested regarding their potential to leach REE from FP. Among them were classical acidophilic microorganisms, as well as various heterotrophic ones, producing organic acids or metal complexing metabolites, or having a high metal tolerance. Larger amounts of REE were leached with the strains Komagataeibacter xylinus, Lactobacillus casei, and Yarrowia lipolytica . Besides the COOH-functionality, also other biotic processes contribute to metal leaching, as comparison with indirect leaching approaches showed. Among the different REE components of the FP preferably the oxidic red dye yttrium europium oxide (YOE) that contain the critical REE yttrium and europium was leached. The results provide the basis for the development of an environmentally friendly recycling process for REE from waste materials.